Factors Increasing Net Income in The Company; Systematic Literatur Review - Lorence Manalu; Winanti Winanti; Masduki Asbari; Fernando Manalu; Ahmad Nafis Ayyasy; Imam Muhammad Rizal; Sefthian Sefthian (PT. BERBAGI TEKNOLOGI SEMESTA, 2026)
This study aims to identify factors that influence the increase in net profit in companies through a Systematic Literature Review approach. Increasing net profit is one of the main objectives of the company, which affects investment decisions and business sustainability. Given the importance of understanding these factors, this research is relevant to provide a comprehensive overview of the elements that affect company profitability. This topic was chosen because although many studies have examined the factors of net profit, there is no research that combines various industry sectors and external factors that affect the financial performance of companies. This research was conducted by collecting and analyzing relevant articles from various scientific journals from 2003 to 2024, by identifying internal factors such as company size, capital structure and operational efficiency, as well as external factors such as macroeconomic conditions, government policies and competition. The results of the analysis show that both internal and external factors significantly affect a firm's net profit, with firm size and operational efficiency having a greater impact. The findings address the issues explored by providing strong evidence regarding the role of external factors that are often overlooked in previous studies. This research makes a significant contribution in understanding the factors that influence net profit, as well as providing practical recommendations for managers to optimize the company's financial performance.